From training to articulation. The experience of Construcciones 1 in extension projects - Cáceres, Marcos; Construcciónes I, Área de la Tecnología y la Producción, Facultad de Arquitectura y Urbanismo, Universidad Nacional Del Nordeste, Resistencia, Chaco. (Instituto de Investigaciones Tecnológicas para el Diseño Ambiental del Hábitat Humano, 2020)
The experience reported in this work is the product of a process developed for several years with different actors and institutions and enriched thanks to the experiences and needs that arose during the process. The activities began in 2009 as training for workers in municipalities in the interior of the Chaco. This initial project was adjusting and growing in commitment through the extension program "The University in the Middle" and the link with other institutions: Faculty of Engineering of the U.N.NE. and the U.E.P. UOCRA N ° 149. Thus we managed, in the successive years of implementation, to articulate the training of workers with the training of the faculty student, promoting the exchange of knowledge and work, bringing our students closer to professional practice in a process continuous feedback.